Daddy Hall : a Biography in 80 Linocuts. - Miller, Tony (Wordless Novels., 2017)
A striking visual saga in linocuts of the life of John 'Daddy' Hall, a man of Mohawk and African-American descent who survived war, capture and slavery to become a pillar of the community in nineteenth-century Owen Sound, Ontario.